(3TQM GHf ZGfe Ydi GdRcGIs - (3CHh SdjeGf OGhhO Hf CMeO GdCZjdi GdQGYis; (3eMeO EHQGgje Hf ZGfes
(3ChdgG (B:s
(3GdMeO ddg GdPi CHGM dYHGOg GdEHGMGJ ef GdeCchdGJ hGdeTQhHGJ CeG HYO agPG TQM YLjH Ydi CHjGJ ai HjGf GdRcGI GdefMaI hZjQgG ddTjN eMeO EHQGgje Hf ZGfe s
(3BNQgG (B:s
(3bGd CHh SdjeGf GdCZjdi YaG Gddg Yfg ced eG CQOJ JbjjOg HMeO dGdg JYGdi hMSf Yhfg hGNJe cJGHi gPG HOYGA GdfHi Udi Gddg Ydjg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(869 d) s
Keywords: (3GdeLGejYs